Self-Organization of Citizens at the Rural Settlements вЂ“ Look Through Pink Glasses - Elena S. Shomina (Социологическая наука и социальная практика, 2020)
For more than 30 years, Russia has been developing “territorial public self-government” – the process of self-organization of citizens at the local level (TOS in Russian). The article considers the development of TOS as a tool for involvement and participation of citizens in local self-government (LSG). In Russia at the beginning of 2020, there were more than 33 thousand TOS, half of them in rural areas. It is a slow transformation of TOS activities (from the distribution of humanitarian aid in the 1990s) before participating in National projects after 2018), as well as changing attitudes towards TOS (from lack of recognition and support – to cooperation and allocation of serious funds, up to presidential grants). On the basis of long-term included observation, positive social practices that are implemented in rural settlements, features of the daily activities of rural TOS, features of rural life, including the nature of development and individual consumption of municipal resources, environmental problems and the seizure of agricultural land and pastures are described. Rural TOS are forced to do more practical things, their projects are more labor-intensive, and the contribution of the residents themselves is more tangible and visible (engineering infrastructure, roads and sidewalks, gasification, electricity and street lighting, garbage collection, and other cultural and leisure projects): a different scale than in the city, but much greater diversity, involvement and initiative of the residents themselves. The positive experience of the TOS of Kameshkovsky rural settlement of the Vladimir region and Novopavlovsky rural settlement of the Krasnodar territory is considered. Numerous social practices are described, as well as the problems encountered in connection with the emergence of municipal districts.